2021
DOI: 10.21037/jgo-20-326
|View full text |Cite
|
Sign up to set email alerts
|

Value of nutrition support therapy in patients with gastrointestinal malignancies: a narrative review and health economic analysis of impact on clinical outcomes in the United States

Abstract: Malnutrition, particularly under-nutrition, is highly prevalent among adult patients with a diagnosis of gastrointestinal (GI) cancer and negatively affects patient outcomes. Malnutrition is associated with clinical and surgical complications for patients undergoing therapy for GI cancers and the costs associated with those complications is a high burden for the US health system. Our objective was to identify high-quality evidence for nutrition support interventions associated with cost savings for patient car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…Pimento et al have recently reported that healthcare costs can be reduced by the implementation of nutrition intervention for patients with gastrointestinal cancers 17 . We agree with that, since the implementation of the ACERTO project changed the nutritional approach in our patients from a staff-oriented perspective to a protocol-oriented protocol, which was absorbed by the multidisciplinary staff of the hospital including not only surgeons but also nurses, dietitians, and physiotherapists.…”
Section: Discussionmentioning
confidence: 99%
“…Pimento et al have recently reported that healthcare costs can be reduced by the implementation of nutrition intervention for patients with gastrointestinal cancers 17 . We agree with that, since the implementation of the ACERTO project changed the nutritional approach in our patients from a staff-oriented perspective to a protocol-oriented protocol, which was absorbed by the multidisciplinary staff of the hospital including not only surgeons but also nurses, dietitians, and physiotherapists.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative immunonutrition and recovery strategies after surgery have significantly decreased postoperative complications and decreased hospital stays. Savings due to the adoption of these measures have been estimated at more than 200 million dollars [ 130 ].…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…In the UK, it was found that the cost of treating a malnourished patient is up to 3 times higher compared to a non-malnourished patient [112] Data from the Netherlands reveal that managing disease-related malnutrition accounted for 4.9% of total healthcare expenditure [118]. US economic modelling based on international health economics data suggested that widely implementing nutrition support in gastrointestinal cancer alone could account for up to US $242 million in Medicare savings each year [119]. Importantly, these savings have been demonstrated in real-world settings, showing that significant cost savings can be achieved by implementing optimal nutrition care in cancer [114,115,120].…”
Section: Integrating Nutrition Into Cancer Care Is Economically Advan...mentioning
confidence: 99%